Farmer Friendly Options for Sterilizing Farm Tools for the Control of Xanthomonas Wilt Disease of Banana - Ocimati, Walter; Tazuba, Anthony Fredrick; Blomme, Guy (Frontiers in Agronomy, 2021)
The adoption of tool sterilization using either 3.5% sodium hypochlorite (JIK) or fire, a core element Xanthomonas wilt (XW) of banana control packages has been poorly adopted hampering XW control in East and Central Africa. JIK is costly and not accessible to the rural poor while repeated heating weakens metal blades of garden tools. Identification of economically viable tool sterilization options is thus crucial for XW management. We explored a range of practices including tool insertion for varying time periods into cold and hot ash, fire and boiling water; tool exposure over varying time periods to the sun while under black or transparent plastic sheets; and washing tools with cold water and laundry soap or detergent. Cleaning with JIK served as a negative control while uncleaned tools as positive control. Like for JIK, no Xanthomonas vasicola pv. musacearum (Xvm) the causal agent of XW was recovered from tools washed with cold water and different laundry soaps or detergents. Culturing Xvm in varying detergent and soap concentrations (0.00125 to 0.035 g/mL), only resulted in growth at lower concentrations of 0.00125 and 0.0025 g/mL. The cleaning effect of soap could thus be due to both an anti-bacterial effect and dislodgment of bacteria from tools. Laundry soaps/ detergents are cheaper than JIK and used for various purposes within and across households, including the resource poor and rural households. They therefore offer a cheaper and convenient tool sterilization alternative. Tool insertion into boiling water was effective from the 40th second and thus a viable alternative. Heating tools in fire required up to a minute to clear all bacteria. The currently recommended 20-40 second heating could thus be inadequate. Repeated heating for 1 minute may also damage tools. Other practices (washing with cold water only, use of solar radiation, repeatedly and forcefully inserting tools into the soil, tool insertion into hot and cold ash for up to 5 min) only reduced Xvm populations on tools, thus not independently recommended. We recommend expanding the tool sterilization options to include washing with soap/ detergents and tool insertion into boiling water for at least 40 seconds.